A Philatelic Excursion with Jeff Hunter in Probability and Matrix Theory. (15th November 2007) - Styan, George P. H.; Trenkler, Götz
Abstract : We present an excursion with Jeff Hunter, visiting some of his research topics. Specifically, we will present some facts about certain people whose work seems to have influenced Jeff in his scientific career; we illustrate our presentation with postage stamps that have been issued in honour of these people. Our main guide is Hunter's two-volume book entitled Mathematical Techniques of Applied Probability (Academic Press, 1983).